Book review: Marie Millet, Vincent Rondot, Frédéric Payraudeau, and Pierre Tallet (eds), Proceedings of the 14th International Conference for Nubian Studies, Paris 2018 (=Kush XX). Cairo: Institut français d'archéologie orientale (IFAO), 2023; ISBN 978-2-72470-988-9 (hardcover); 1004 pages (2 volumes) - Robert J. Stark (Polish Archaeology in the Mediterranean)
The publication of the proceedings of the 14th International Conference for Nubian Studies, collaboratively hosted by the Musée du Louvre and Sorbonne Université from 10 to 15 September 2018, marks the most recent in a prestigious line of such collective volumes. The focus of the proceedings of the quadrennially held conference of the International Society for Nubian Studies (ISNS) centers around investigations of the geographic region of ancient Nubia, adjacent zones of interconnectivity, and associated contemporary cultural aspects in what is today parts of Sudan and Egypt. The published proceedings of each ISNS conference effectively provide a field-encapsulating benchmark of cultural heritage-oriented research in Nubian and associated contexts, signposting research trends and projects, the state of discourse within Nubiology as a discipline, as well as where ongoing and future research may be heading.